Mandatory wage posting, bargaining and the gender wage gap - Wolfgang Frimmel; Bernhard Schmidpeter; Rene Wiesinger; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2022)
We evaluate whether revealing wage information in job vacancies is able to change the gender wage gap. In 2011, the Austrian Equal Treatment Law mandated every vacancy to include a minimum wage offer. This mandatory wage information makes the employer's willingness to pay and the value of outside options more salient to job applicants, thus changing bargaining options. Our general results show a small effect of the provision of wage information, reducing the gender gap somewhat. Taking up the bargaining argumentation, we split the sample into vacancies where a higher or a lower bargaining power of firms is to be expected and find a strong and significant reduction of the gender wage gap for jobs which are immediately available and need to be filled urgently. The effect is driven by an increase in female wages. There is no such effect for jobs positions which are not urgently vacant. There is no evidence for changes in vacancy characteristics, meaning the estimated effects come from the provision of wage information rather than different job descriptions and amenities offers. We also show that effects are unlikely to come from changes in the composition of employees and firms as well as from increased returns to labor market experience.
Keywords: J31; J23; J63; 330; mandatory wage posting; pay transparency law; gender wage gap; job postings; quantile DID